Static Video Summarization Using Video Coding Features with Frame-level Temporal Sub-Sampling and Deep Learning - Issa, Obada (2023)
There is an abundance of digital video content due to the cloud’s phenomenal growth and security footage, it is therefore essential to summarize these videos in data centers. This paper offers innovative approaches to the problem of key-frame extraction for the purpose of video summarization. Our approach includes feature variables extracted from the bit streams of coded videos, followed by optional stepwise regression for dimensionality reduction. Once the features are extracted and reduced in dimensionality, we apply innovate frame-level temporal sub-sampling techniques followed by training and testing using deep learning architectures. The frame-level temporal subsampling techniques are based on cosine similarity and PCA projections of feature vectors. We create three different learning architectures by utilizing LSTM networks, 1D-CNN networks, and Random Forests. The four most popular video summarization datasets, namely, TVSum, SumMe, OVP, and VSUMM are used to evaluate the accuracy of the proposed solutions. This includes the Precision, Recall, F-score measures, and computational time. It is shown that the proposed solutions when trained and tested on all subjective user summaries, achieved F-scores of 0.79, 0.74, 0.88, and 0.81, respectively, for the aforementioned datasets, showing clear improvements over prior studies.